Duet in diamonds. - Burke, John frey50 (G. P. Putnam's Sons New York, 1972)
The flamboyant saga of Lillian Russell and Diamond Jim Brady in America's gilded age
Keywords: James Buchanan Brady; Helen Leonard -- aka Lillian Russell -- Singer; Social life and customs -- American Life